The temporal, spatial and population heterogeneity of the associations between ambient temperature and injury by animal in China: A nationwide case-crossover study - Weiquan Zeng; Pengpeng Ye; Mengen Guo; Yuan Wang; Jianxiong Hu; Xiao Deng; Guanhao He; Ye Jin; Tao Liu; Cuirong Ji; Sujuan Chen; Leilei Duan; et al. (Ecotoxicology and Environmental Safety)
Introduction: This study aimed to examine the temporal, spatial and population heterogeneity in the association between temperature and injury by animal in China and to assess the future burden attributed to temperature changes. Methods: Injury by specific animal data during 2006–2017 and 2019–2021 were obtained from National Injury Surveillance System in China, and meteorological data were obtained from the fifth generation of European ReAnalysis-Land. Conditional logistic regression combined with a distributed lag nonlinear model was applied to investigate the association of temperature with injury by animal. Additionally, we projected future trends in animal-related injury burden linked to temperature changes. Results: This study included a total of 859,321 injury cases by animal. The excess risk (ER) on injury by animal increased 1.57 % [95 % confidence interval (CI): 1.48 %-1.67 %] for a 1°C temperature rise with much higher risk for injury by non-mammalian (ER=7.54 %, 95 %CI: 7.12 %-7.96 %) than that for injury by mammalian (ER=1.75 %, 95 %CI: 1.62 %-1.87 %). Among injury by mammalian, dog bites showed the highest risk (ER=2.01 %, 95 %CI: 1.86 %-2.15 %), while snake injury was most affected by temperature (ER=11.82 %, 95 %CI: 10.44 %-13.21 %) among injury by non-mammalian. We observed significant population heterogeneity with higher ER for male, children < 5 years and farmer. We also observed spatial heterogeneity with higher risk for warm region or southern and central China. Temporally, the top three associations between temperature and animal injury risk were observed in 2009, 2020 and 2010, however, the difference was not statistically significant. Projections indicate that under the SSP585 scenario, the temperature-attributable fraction of animal-related injuries in China will increase by 13.89 % (95 % CI: 9.19 %-18.63 %) in the 2090 s compared to the 2010s baseline. Conclusions: High temperature significantly increase injury by animal with significant spatial, temporal, population, and animal heterogeneity. Future temperature rise will increase the burden of injury by animal.